Water Use Efficiency Evaluation in Deficit Irrigation and Partial Root Zone Drying in Potato (Solanum tuberosum L.) - A. Asadi; H.R. Khazaie; J. Nabati (مجله آب و خاک, 2023)
IntroductionDue to climate change, one of the limiting factors of crop production is environmental stress which, by disrupting the natural metabolism of the plant, limit plant growth and finally reduce crop production. Drought stress causes the greatest reduction in crop productivity compared to other environmental stresses. Therefore, the use of methods to reduce water consumption in agriculture is more important due to the lack of freshwater resources. Increasing water use efficiency and maintaining plant yield by reducing water consumption has a particular importance for crop production and should be paid special attention. Drought stress reduces photosynthesis, stomatal conductance, biomass, growth and consequently plant yield. The effects of drought stress on the yield of plants such as potatoes (Solanum tuberosum L.), wheat (Triticum aestivum L.), rice (Oryza sativa L.) etc., which play an important role in the nutrition and food of the world, has a great importance. Achieving the desired soil moisture range is one of the most important approaches to increase water use efficiency and not significantly reduce yield. For this goal, a factorial experiment was conducted in a completely randomized design with five replications in the research greenhouse of Ferdowsi University of Mashhad.Materials and MethodsFactors studied in this experiment included three levels of irrigation 1- full irrigation (100% of field capacity), 2- medium drought stress (70% of field capacity), 3- partial root-zone drying (70% of field capacity), time of induction of water stress (two weeks after planting and 50% at flowering time) and two levels of phosphate (CaH4[Po4]2 H2O) fertilizer (based on soil analysis (25 mg.kg-1) and adding 25% more than recommended (31 mg.kg-1)) at the beginning of the period phosphate was mixed with soil inside the pot in greenhouse condition. Fontane potato cultivar was used in this study. In irrigation treatments, one part of the pots was stressed two weeks after planting and the second part of the pots were fully irrigated until the beginning of flowering and irrigation treatments were applied at 50% flowering stage. From the prepared samples, membrane stability index, osmotic potential, and relative water content were measured in the laboratory and at the end of experiment, plant height, tuber weight, biomass and plant water use efficiency were measured. Minitab 18 software was used to analyze the data.Results and DiscussionThe results showed that with increasing phosphate fertilizer from 25 mg.kg-1 to 31 mg.kg-1, plant biomass increased significantly and in all treatments biomass increased between 2 to 28% . Partial root-zone drying treatment showed a 17.4% increase in biomass. In the medium drought stress treatment, the total growth period and phosphorus level of 31 mg.kg-1, the lowest water use efficiency was observed, and there was no significant difference in the medium drought stress treatment of the total growth period and the phosphorus level of 25 mg.kg-1. Partial root-zone drying treatment of roots from flowering time and 31 mg.kg-1 P, with full irrigation treatment 25 mg.kg-1 P have the same water use efficiency, but the performance of this treatment  compared to full irrigation treatment was reduced by 28%. Water use efficiency in partial root-zone drying (intermittent irrigation) has increased compared to traditional irrigation, which indicates a more optimum use of water in the medium drought stress method. Full irrigation treatment had the highest tuber weight per plant and partial root-zone drying during the growing season treatment had the lowest tuber weight per plant (65%) compared to full irrigation. The partial root-zone drying treatment after flowering, ranked second after full irrigation treatment, for tuber weight per plant and more tuber weight per plant compared to other drought treatments. Using 31 mg.kg-1 phosphate, tuber weight per plant in full irrigation treatment reached 332 g.plant-1 which increased by 13% and was significantly different from all treatments. With increasing phosphate level from 25 mg.kg-1 to 31 mg.kg-1, in the partial root-zone drying treatment from flowering time, tuber weight per plant increased by 28% to 207 g.plant-1. Tuber weight per plant in other drought treatments decreased with increasing phosphate level from 25 mg.kg-1 to 31 mg.kg-1, although this decrease was not statistically significant. ConclusionCompared to deficit irrigated methods, partial root-zone drying from the beginning of growth and full irrigation has the ability to use available nitrogen at the end of the growing season and has more greenery than other drought treatments. This effect probably explains the filling of the gland tubers at the end of the growing season and thus the keeping of yieldyield production. The best methods for saving water consumption and maintaining the yield, the partial root-zone drying methods is better than the medium drought stress method.